Educational Quality Management in The Implementation of Holistic Integrative Early Childhood School in Jambi Province - Anisyah, Nur; Marwazi; Iskandar (JOYCED: Journal of Early Childhood Education, 2025)
This study aims to examine the quality management of education in the implementation of Holistic Integrative Early Childhood Education (PAUD) in three TKIT institutions, namely TKIT Al-Muthmainnah Jambi City, TKIT Aulia Muaro Bulian, and TKIT Diniyyah Al-Azhar Muaro Bungo Jambi Province. The results of the study indicate that the quality management model of education in the three TKIT institutions integrates aspects of education, health, nutrition, care, and child protection. The principals implement periodic supervision and evaluation, systematic program planning, teacher competency development, and context-based learning experiences with the principle of continuous improvement. Although there are obstacles such as limited teacher understanding, infrastructure, and parental participation, support from parents, the government, universities, and community institutions strengthens the implementation of the program. The principals' strategies include developing teacher competencies, intensive collaboration with parents, learning innovation through out-of-class activities, quality evaluation using the PDCA (Plan-Do-Check-Act) principle, and collaborative networks with external parties.